Lena Herzog - Barbieri, Giuseppe; Burini, Silvia (Skira, 2024)
This first comprehensive monograph on the work of Lena Herzog is an exhaustive review of three decades of activity, described in essays by professors Silvia Burini and Giuseppe Barbieri of Ca’ Foscari University in Venice. Lena Herzog’s undaunted and engaging look spans over boundaries and chasms between different levels of life, time, and memory. Her work investigates the universal mystery of being human, from the Cabinets of Wonder and Curiosities of the 18th and 19th centuries to the hollowed out rock formations atop of tepuis in Amazonia, from the deep rituals of the West to the emptiness of nameless lands in the Far East. The various portfolios, here transversally arranged, provide a fascinating cartography of our time and history. Through innovative experimentation, Lena Herzog fuses Renaissance engraving practices, early techniques of developing and printing photographic images, and cutting edge virtual reality and immersive technologies. In her latest projects, she confronts and denounces the extinction of thousands of languages and foretells the possible and final collapse of the planet. These are images between shadow and light, which, as in Goya, pursue the truth of things, gestures, and faces, and in which we find echoes of her childhood phantoms at the foothills of the Ural Mountains
Keywords: Herzog, Lena -- 1970-